Pelaksanaan Perlindungan Hukum Bagi Konsumen terhadap Peredaran Makanan yang Telah Kedaluwarsa di Pasar Kreneng Denpasar - I Putu Gede Wiramahendra; I Nyoman Budiartha; Ni Komang Arini Styawati (Warmadewa Press, 2022)
Expired food is frequently circulated or traded in traditional markets. Premised upon, the issue is related to legal protection towards the circulation of outdated food for consumers, particularly at Denpasar Kreneng Market, and the elements create difficulties to obtain legal protection within the issue at hand. This study is an example of an empirical legal study. Judging upon this study's findings, it is reasonable to state that customers who were disadvantaged as both a consequence of trade and circulation of expired food are subjected both to repressive and preventive approaches for their legal protection. Meanwhile, the absence of reports made to the Denpasar Dispute Settlement Agency (BPSK) by persons who complained about sellers and distributors of expired food, as well as insufficient product data listings, hampered the community's opportunity to get legal protection. These might occur as a result of the public's attitudes and mentality, which encourages them to just be hesitant to disclose harmful commercial practices